Developing a biotechnology practicum guidebook for producing nata de coco to increase students’ learning outcomes - Utari, Tri; Lubis, Khairiza; Rahmah, Siti (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2023)
This study aims to produce a product in the form of a practical work guidebook for making nata de coco to help smooth the practical work process, which was adapted from the development of a 4-D model. The 4-D model consists of 4 stages, namely the stage of defining, designing, developing and disseminating. The level of feasibility of the practical work guidebook is carried out through a validation process by material experts, media experts and supported by responses from teachers and students. The results of the validation carried out by material expert validators and media experts were categorized as "Very Eligible" with 95% and 92.85% respectively. Meanwhile, the teacher's response and the student's response were also categorized as "Good" with 95% and 99% respectively. This is supported by the effectiveness test conducted in the cognitive (pretest and posttest) and psychomotor domains. In the cognitive domain, it shows a fairly good score, which has a difference between the initial ability (pretest) and the final ability (posttest) with an average value of 46.32 to 78.12. The t test also shows a significant value of 0.000 with the "medium" N-Gain category (60.6%). The psychomotor domain also produced a score with an average of 82 of the overall score or the “Excellent” category. Based on the research data, it can be interpreted that the book developed has a considerable influence on practical learning outcomes and can facilitate students to learn, both with educators and independently in making nata de coco which is packaged in an attractive and easy to understand manner.